Quality Oil Company. D. L. Dodd Shell Service Station at Kernersville, N.C. - Unknown (Forsyth County Public Library, 2008)
Photo was made in the 1930s. The Quality Oil Company granted permission to the Forsyth County Public Library to reproduce these images for the collection and to make them available on Digital Forsyth.
Quality Oil Company. D. L. Dodd Shell Service Station at Kernersville, N.C. The sign on the building says "Dodd's Grocery."
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works